A nanoporous polymer film as a diffuser as well as a light extraction component for top emitting organic light emitting diodes with a strong microcavity structure. Issue 16 (6th April 2016) - Pyo, Beom; Joo, Chul Woong; Kim, Hyung Suk; Kwon, Byoung-Hwa; Lee, Jeong-Ik; Lee, Jonghee; Suh, Min Chul
Abstract : To improve the viewing angle characteristic as well as the light extraction effect of strong microcavity devices, we introduced a nanoporous polymer film (NPF). Abstract : To improve the viewing angle characteristic as well as the light extraction effect of strong microcavity devices, we fabricated a nanoporous polymer film (NPF) as a scattering medium as well as a light extraction component. We designed two types of organic light emitting diodes (OLEDs) with a strong microcavity effect by changing the thickness of the hole transport layer (HTL; e.g. 30 nm and 60 nm) to investigate two different scattering effects of the NPF. Very interestingly, we could observe a significant enhancement of the external quantum efficiency (EQE) for each device (30 nm thick HTL: 18.0%, 60 nm thick HTL: 31.6%) when we attached a NPF formed on a 125 μm thick PET film coated with the NPF. Furthermore, the NPF successfully suppressed the viewing angle dependence to realize ideal angular emission even in the two extreme microcavity conditions although they are still different from that of a Lambertian distribution.